AB0200 The Expression of Angiotensin and Endothelin Receptors on PBMCS of Patients with Systemic Sclerosis and their Clinical Relevance. (10th June 2014) - Rademacher, J.; Guenther, J.; Kill, A.; Siegert, E.; Riemekasten, G.
Abstract : Background: Stimulating autoantibodies against angiotensin (II) type-1 receptor (AT1R) and endothelin type-A receptor (ETAR) are present in the majority of systemic sclerosis (SSc) patients. High antibody (ab) levels are associated with severe clinical disease manifestations and with mortality. Current data indicates their contribution in disease pathogenesis. Male patients often exhibit SSc symptoms early in the disease and often have cardiac involvement and very progressive fibrotic lung disease associated with high levels of the profibrotic chemokine CCL18. Since anti-AT1R/ETAR ab levels are similar in female and male SSc patients we asked whether differences in the receptor expression exist that could explain sex differences presented especially in the early phase of SSc. Objectives: To identify whether expression of angiotensin-II and endothelin receptors on peripheral blood mononuclear cells (PBMC) is influenced by sex, by disease duration or by organ manifestations in SSc patients and to analyze the functional relevance of receptor expression by measuring ab-mediated CCL18 production in PBMC with known receptor expression of AT1R and ETAR as well as their respective functional counterparts AT2R and ETBR. Methods: Protein and mRNA receptor expression (for AT1R, AT2R, ETAR and ETBR) was measured on PBMC of 30 SSc patients by flow cytometry and by real-time PCR, respectively and correlated with sex, disease duration, and clinical findings of these patients. In addition, PBMCs of 11 healthy donors were similarly analyzed for receptor expression and were in vitro stimulated with affinity purified immunglobulin G (IgG) of either SSc patients or healthy donors. Unstimulated PBMC were used as further control. Afterwards the concentration of CCL18 was measured in the supernatants by ELISA and was correlated with receptor expression by Spearman rank correlation. Results: SSc patients with lung fibrosis and left ventricular dysfunction have higher expression of ETAR and ETBR compared to those without these symptoms (p<0, 05 for both receptors). In addition, male patients present significantly higher levels of receptor density as well as more receptor positive cells compared to female SSc patients for all 4 examined receptors. AT1R, AT2R, ETAR and ETBR expression correlated significantly with the modified Rodnan Skin Score. AT1R density was highest in early disease and the expression of AT1R, AT2R, ETAR and ETBR correlated significantly negative with the time since onset of Raynaud's phenomenon with various correlation coefficients for the different PBMC subsets. After stimulation of PBMC with SSc-IgG we observed a significant positive correlation between the concentration of CCL18 in the supernatant and the ratio of AT1R/AT2R protein expression on CD14+ (r=0, 73; p=0, 03). Conclusions: Angiotensin and endothelin receptor expressions on PBMC could explain sex differences in SSc patients and different effects of the antibodies among individual SSc patients. References: Riemekasten G et al. Involvement of functional autoantibodies against vascular receptors in systemic sclerosis. Ann Rheum Dis 2011;70(3):530-6 Tiev KP et al. Serum CC chemokine ligand-18 predicts lung disease worsening in systemic sclerosis. Eur Respir J. 2011;38(6):1355-60 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5024